Analysis of precious metal (gold) investment management at pt. antam tbk from a sharia economic perspective - Madani Amir, Moch. Sayyid Salsabila; Wazin, Wazin; Peristiwo, Hadi (Institute of Computer Science (IOCS), 2024)
Investment is a commitment to save a certain amount of funds to obtain a certain amount of profit in the future. Thus, the aim of this research is how to manage precious metal investment and how precious metal investment is viewed from an Islamic perspective. The approach taken in this research uses a qualitative approach with the library research method. The data sources in this research use primary and secondary sources. Primary includes journal articles, E-Books, and other internet media. While secondary such as online proceedings, magazines, newspapers, and word press. Meanwhile, the data collection technique in this research is collecting from the sources that have been mentioned and then classifying them to conclude. The analysis technique used is descriptive analysis. The results of this research show that explaining sharia principles in investing is important as a guide for society. investment activities explicitly or implicitly in a number of verses of the Koran and the sunnah of the Prophet Muhammad saw. who has been in business and has been Mecca's financial support partner for a long time. The conclusion of this research explains that based on the DSN MUI Fatwa Number 77/DSN-MUI/IV/2010 concerning non-cash buying and selling of gold, it is decided that if there is a non-cash buying and selling of gold, either through murabahah or through regular buying and selling, the law is permissible. only, as long as the gold is not an official medium of exchange